2015
DOI: 10.1186/s12891-015-0638-7
|View full text |Cite
|
Sign up to set email alerts
|

Reliability, validity, sensitivity and internal consistency of the ICF based Basic Mobility Scale for measuring the mobility of patients with musculoskeletal problems in the acute hospital setting: a prospective study

Abstract: BackgroundThe assessment of mobility is important in the acute care setting. Existing tests suffer from limitations. The aim of the study was to examine the inter-rater reliability, the validity, the sensitivity to change, and the internal consistency of an ICF based scale.MethodsIn a prospective study inpatients in the acute care setting with restricted mobility aged above 50 years assigned to rehabilitative treatment were included. Assessment of subscales of the Functional Independence Measure (FIM) and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Among the functional scales used in this study, ICF-BMS detected the highest percentage of participants who reached this clinically important threshold (72.5%) for which a 7point variation was considered [21]. FSS-ICU is considered feasible to perform in an ICU and had an MCID estimated interval of 3 points [33], which was reached by 15 (37.5%) patients from our study.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Among the functional scales used in this study, ICF-BMS detected the highest percentage of participants who reached this clinically important threshold (72.5%) for which a 7point variation was considered [21]. FSS-ICU is considered feasible to perform in an ICU and had an MCID estimated interval of 3 points [33], which was reached by 15 (37.5%) patients from our study.…”
Section: Discussionmentioning
confidence: 58%
“…e large effect sizes for the functionality outcome reaffirm the importance of following an exercise protocol for this population, especially when we assess them by the ICF-BMS scale involving mobility activities, for instance, getting in/out of their bed to climbing stairs, and that the improvement level was 72.5% by reaching MCID, while 52.5% of the patients had the floor effect at ICU discharge. is did not occur in the study by Pieber et al [21], where the interrater reliability, validity, sensitivity to change, and internal consistency of the same scale were evaluated and showed that it was not vulnerable to floor-ceiling effect.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…According to Fukunaga, Saitou, Harada, Hakamata, & Kagawa, (2015) stated that the mobility measurement instrument has an ICC value higher than 0.8 so it can be recommended to be used to measure the status of elderly mobility by testing on various units or research sites. Pieber, Herceg, Paternostro-Sluga, (2015) stated that the measuring instrument used to measure the mobility status of the elderly that is based on the International Classification of Functioning, Disability and Health useful and reliable measuring instrument with a valid ICC value of 0.85 (95% CI: 0.81-0.88). Studies conducted by Park, (2017) showed that the intraclass correlation used in the Timed Up and Go Test measuring instrument has a value higher than 0.90 so that the instrument can be used as a reference in the preparation of another mobility measurement instrument.…”
Section: Resultsmentioning
confidence: 99%
“…So far, various measurement tools have been developed to assess and monitor the independent mobility of hospitalized patients [13][14][15][16][17][18][19], but it appears that the majority of physiotherapists working in hospitals currently do not use these tools as a standard part of their care [20]. Underlying reasons for not adopting the available instruments are that they are too time consuming to complete during usual care, too time-consuming to analyze or they have been designed for only a small part of the total hospital population [20].…”
Section: Introductionmentioning
confidence: 99%